An integrative systems approach identifies novel candidates in Marfan syndrome-related pathophysiology - Bhushan, Raghu; Zaradzki, Marcin; Kallenbach, Klaus (Journal of cellular and molecular medicine, 2019)
Marfan syndrome (MFS) is an autosomal dominant genetic disorder caused by mutations in the FBN1 gene. Although many peripheral tissues are affected, aortic complications, such as dilation, dissection and rupture, are the leading causes of MFS-related mortality. Aberrant TGF-beta signalling plays a major role in the pathophysiology of MFS. However, the contributing mechanisms are still poorly understood. Here, we aimed at identifying novel aorta-specific pathways involved in the pathophysiology of MFS. For this purpose, we employed the Fbn1 under-expressing mgR/mgR mouse model of MFS. We performed RNA-sequencing of aortic tissues of 9-week-old mgR/mgR mice compared with wild-type (WT) mice. With a false discovery rate <5%, our analysis revealed 248 genes to be differentially regulated including 20 genes previously unrelated with MFS-related pathology. Among these, we identified Igfbp2, Ccl8, Spp1, Mylk2, Mfap4, Dsp and H19. We confirmed the expression of regulated genes by quantitative real-time PCR. Pathway classification revealed transcript signatures involved in chemokine signalling, cardiac muscle contraction, dilated and hypertrophic cardiomyopathy. Furthermore, our immunoblot analysis of aortic tissues revealed altered regulation of pSmad2 signalling, Perk1/2, Igfbp2, Mfap4, Ccl8 and Mylk2 protein levels in mgR/mgR vs WT mice. Together, our integrative systems approach identified several novel factors associated with MFS-aortic-specific pathophysiology that might offer potential novel therapeutic targets for MFS.